Elemen dan Faktor Governansi Inovasi Pelayanan Publik Pemerintah - Lesmana Rian Andhika (Balitbangda Provinsi Lampung, 2018)
Many innovations that have been produced in the government public services but was not able to demonstrate a more significant benefit. Governance innovation provides the framework of how innovation can manage. A qualitative descriptive method used in this research, the source of the data collected in deductive from some scientific literature and government regulations. This study aims to describe the elements and factors governance innovation in public service. The results of this research show that the governance innovation contributes to the better in the government public service. Governance innovations can implement by analyzing institutional factors as executor, an actor as policy decision makers and citizen participation as a recipient of the government public service innovation.